Asuhan Keperawatan Pada Pasien Gagal Ginjal Kronis Dengan Hipertensi Pre-HD Dengan Menggunakan Penerapan Terapi Musik Klasik: Nursing Care In Chronic Renal Failure Patients With Pre-Hd Hypertension Using Application Of Classical Music Therapy - Sinta Wijayanti (Madago Nursing Journal, 2021)
Chronic renal failure (CRF) is the final stage of failure of the nephrons to maintain their function due to the progressive destruction of nephrons which are irreversible and require renal therapy. One of the renal therapy is hemodialysis. Hemodialysis is a therapy used when the kidneys are unable to carry out their function to remove uremic toxins and talk about body electrolytes and have complications of hypertension. In hemodialysis patients, uncontrolled hypertension can increase the prevalence of cardiovascular disease so it is a very important factor in the prognosis of cardiovascular complications in chronic chronic failure patients with hypertension. Many non-pharmacological therapies that have been developed in the world of nursing include classical music therapy. The goal of this therapy is to identify and analyze the patient's blood pressure before and after being given classical music therapy. The design of this study used the applied research approach method once a day for 6 days. The number of samples taken was 10 samples that fit the inclusion criteria. The research instruments used were MP3 Player, Mozart classical music entitled Eline Kleine Nachtmusik, K. 525: I. Allegro, headphones, sphygnomanometer clock observation sheet, and stethoscope. The results of this study show that there is a change in pressure after being given classical music therapy because music can easily be accepted by the hearing organs and easily captured by the brain so that it makes a person more relaxed which causes blood vessels to dilate so that it can lower blood pressure. The conclusion of the results of this study is to present classical music therapy in lowering blood pressure, which is effective in lowering blood pressure.